2017
DOI: 10.5222/jaren.2017.1012
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Health of Women During Pospartum Period and Affecting Risk Factors

Abstract: ÖZ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
9
0
5
Order By: Relevance
“…Nitekim Genç Koyucu ve Demirci (37) yaptığı derleme çalışmasında da, doğum eyleminin başarılı bir şekilde sonlanmasında bakım veren kişilerin önemli rolleri olduğu bildirilmektedir. Doğum sonrası anne memnuniyetinin düşük olması ve olumsuz bir doğum deneyimi, kadında erken veya geç postpartum depresyona zemin hazırlayabildiği gibi, posttravmatik stres bozukluğu, gelecek dönemlerde cinsel ilişki ile ilgili olumsuz düşünceler, istenmeyen gebeliklerde kürtaj, sonraki doğumlarda sezeryan isteği, anne-bebek bağlanmasında yetersizlik, emzirme sorunları, bebeği ihmal gibi durumlara neden olabileceği bildirilmektedir (14,21,38) . Ayrıca Weeks ve ark.…”
Section: Discussionunclassified
“…Nitekim Genç Koyucu ve Demirci (37) yaptığı derleme çalışmasında da, doğum eyleminin başarılı bir şekilde sonlanmasında bakım veren kişilerin önemli rolleri olduğu bildirilmektedir. Doğum sonrası anne memnuniyetinin düşük olması ve olumsuz bir doğum deneyimi, kadında erken veya geç postpartum depresyona zemin hazırlayabildiği gibi, posttravmatik stres bozukluğu, gelecek dönemlerde cinsel ilişki ile ilgili olumsuz düşünceler, istenmeyen gebeliklerde kürtaj, sonraki doğumlarda sezeryan isteği, anne-bebek bağlanmasında yetersizlik, emzirme sorunları, bebeği ihmal gibi durumlara neden olabileceği bildirilmektedir (14,21,38) . Ayrıca Weeks ve ark.…”
Section: Discussionunclassified
“…3,[23][24][25] The studies conducted in various regions of Turkey in various periods of time have reported PPD prevalences ranging from 15.4% to 51%. [5][6][7] As for new mothers in Turkey, pregnancy preparation in various health institutions, preparation for postnatal period with pregnancy follow-ups, follow-up of totally six puerperants in the hospital and at home three times each during the postnatal period, social support provided by the family and the close environment, and women's and mothers' prestige in society are the positive elements in terms of protection from PPD. 18,26 However, the prevalence of PPD obtained from the study, though consistent with rates seen in the world and in Turkey, is close to the upper limit.…”
Section: Discussionmentioning
confidence: 99%
“…4 The studies conducted in Turkey to determine the frequency of PPD observed the prevalence of this disorder in the range from 15.4% to 51.3%. [5][6][7] The stage of infancy is a period when growth in the brain and dependence on the mother occur together. The growth and development of the baby depend on intrinsic (biological) and extrinsic (nutrition, bonding) factors.…”
mentioning
confidence: 99%
“…Türkiye'de ise bu oran %15.4-51.3 arasında değişiklik göstermektedir. 2,30,31 PPD'nin nedeni henüz tam olarak bilinmemektedir. Genetik etmenler, hormonal değişimler, hipotalamik-pituater-adrenal aksın ve nörotransmitter, kolesterol ve yağ asidi anormalliklerin postpartum depresyon üzerine etkisinin olabileceği düşünülmektedir.…”
Section: Postpartum Dönem Ve Mental Sağlıkunclassified